A Review of Toxoplasmosis and Neosporosis in Water Buffalo (Bubalus bubalis) - Barros, Luiz Daniel de; Garcia, Joao Luis; Saraiva Bresciani, Katia Denise [UNESP]; Cardim, Sergio Tosi; Storte, Victor Sesnik; Headley, Selwyn Arlington (Frontiers Media Sa, 2020)
Toxoplasmosis and neosporosis are diseases with worldwide distribution that are associated with reproductive problems in livestock and responsible for economic losses. This review presents an overview of the current knowledge relative to these diseases in water buffalo (Bubalus bubalis). In general, buffalo are considered resistant to clinical toxoplasmosis because there are studies only reporting serological evidence of natural infection in these animals. Studies have described age, poor hygienic status of the farm, and presence of cats as risk factors for the development ofToxoplasma gondiiinfection in buffalo. It must be highlighted that buffalo meat, which does not receive adequate freezing treatment, could be a potential source for toxoplasmic human infection as well as the importance of raw buffalo milk in the transmission of toxoplasmosis to human beings.Neospora caninumis considered one of the major causes of abortion and responsible for huge economic losses in cattle. Vertical transmission is the main route to infect calves, and is responsible for maintaining the parasite within a herd. In buffalo, vertical transmission is also described; moreover, although there are indications thatN. caninummay be associated with abortion in dairy buffalo, the reproductive importance of neosporosis is apparently lower in buffalo relative to cattle. Most studies have identified a higher time of exposition toN. caninumoocysts relative to age. The household system was also described as a risk factor for infection, possibly due to persistent contact between the home-raised buffalo and canids. The fetal immune competence of buffalo is similar to bovine, and buffalo fetus are highly susceptible to infection during the first trimester of pregnancy, indicating thatN. caninummay be an abortigenic agent in buffaloes. Alternatively, it is interesting to note there is evidence that the inflammatory response in pregnant buffalo infected withN. caninumis mild enough to avoid abortion in most cases. It is proposed that the possible transmission of toxoplasmosis through unprocessed milk and buffalo meat may occur, which is important in terms of public health. Additionally, there is strong evidence to suggest thatN. caninummay be associated with abortion in buffalo.
Keywords: Toxoplasma gondii; Neospora caninum; water buffalo; Bubalus bubalis; epidemiology